Postpartum Intrauterine Device Placement in an Unmarried Adolescent Mother: Clinical Justification and Legal Considerations in Indonesia - A Case Report - Hilda Herman; Muhammad Syarif (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2026)
Adolescent pregnancy is a global public health concern associated with increased maternal and neonatal morbidity and mortality, particularly among very young adolescents, whose physical, psychological, and social readiness for pregnancy is often inadequate. Postpartum contraception is a critical strategy to prevent rapid repeat pregnancies. A 15-year-old unmarried primigravida subsequently delivered a live infant. Due to her young age and high risk of repeat pregnancy, postpartum contraceptive counseling was provided. After a comprehensive explanation was given to the patient and her parents, informed consent was obtained from the parents, and a postpartum IUD was inserted to prevent subsequent pregnancy. The procedure was performed without complications, and the patient was scheduled for regular follow-up and psychosocial support. Adolescent mothers (aged 10–19 years) face higher risks of preeclampsia, anemia, and maternal mortality, while their infants are at increased risk of low birth weight, preterm birth, and stillbirth. Recurrent pregnancies with short interpregnancy intervals may further increase these risks. In Indonesia, adolescent reproductive health services are regulated under Government Regulation No. 28 of 2024, which implements the Health Law No. 17 of 2023 and includes access to contraception as part of adolescent reproductive health services. Postpartum IUD insertion in an adolescent mother is clinically appropriate, ethically acceptable, and legally permissible with parental consent, adequate clinical documentation and careful legal consideration to ensure patient safety and protect healthcare providers. Nevertheless, attention to the patient’s religious and sociocultural background remains important to ensure that contraceptive counseling is respectful, patient-centered, and culturally sensitive.